Association of human leukocyte antigen with precursor-B acute lymphoblastic leukaemia (pre-B ALL) in Malays - Hassan, Norfarazieda (2013)
Acute Lymphoblastic Leukaemia (ALL) is one of the leukaemia subdivisions and is a malignant disorder of lymphoid progenitor cells originating from the marrow affecting both children and adults. Pathogenesis and epidemiologic studies of leukaemia in some population strongly suggest that this disease has an inherited basis and described an increase in allele frequency of HLA antigens that contribute as one of the risk factors. Thus, polymorphisms and different HLA genetic make-up in different ethnic groups make it crucial to study the disease in each population. Malays make up the largest population in Malaysia and the incidence of lymphoid leukaemia has also been reported to be highest in this group. It is hypothesised that there is an increased frequency of certain Class II (HLA-DRB1) alleles and also increase in levels of soluble HLA-DRB1 in ALL patients. The objectives of this study were to identify the HLA-DRB1 alleles associated with ALL patients of Malay ethnicity in Malaysia, and further sequence the identified risk alleles, and determine the soluble HLA levels in plasma in those patients compared to the healthy population. HLA-DNA Typing Class II was performed in pre-B ALL patients (n=42) by PCR-SSO (Polymerase chain reaction, sequence-specific oligonucleotides) and the data of HLA allele genotypes were compared with available data from healthy Malay population (n=1445). Furthermore, the plasma levels of soluble HLA class II (sHLA-DRB1) in patients (n=30) and controls (n=31) were determined by sandwich Enzyme-linked immunosorbent assay (ELISA). DNA sequencing of specific HLADRB1 alleles for the risk and associated alleles was also carried out on exon 2 by Sequence based typing (SBT) approach. Results show that there were higher allelic distribution of specific HLA-DRB1 alleles; HLA-DRB1*03 (P value=0.001, OR=2.92, 95% CI=1.47-5.80) and also –DRB1*16 (P value=0.001, OR=2.76, 95% CI=1.30-5.87) observed among Malay pre-B ALL patients. On the other hand, significant decrease in HLA-DRB1*07 (P value=0.032, OR=0.47, 95% CI=0.17- 1.28) and -DRB1*12 (P value=0.008, OR=0.59, CI=0.33-1.03) were seen in these patients, would suggest protective potential for the disease. Further analysis by SBT was able to clarify the resolution of risk alleles, which were HLA-DRB1*03:01:01 and HLA-DRB1*16:02:01, respectively. Polymorphisms were observed between DNA sequences of polymorphic exon 2 of patient and control groups for –DRB1*03 but not –DRB1*16. An increase in levels of soluble HLA-DRB1 in plasma also was detected in the ALL patients (0.260 ± 0.057 μg/mL) compared to normal individuals (0.051 ± 0.007 μg/mL) with p value of 0.001. The results obtained support the earlier hypothesis and suggest that HLA Class II antigens are the susceptible genes and also as possible biomarker for ALL. This investigation may contribute to aetiology and pathogenesis studies on ALL and identify HLA as potential genetic risk markers or as cancer biomarkers, and also as reference for future studies.